Evaluasi Higiene Industri Rumah Makan Khas Batak Kelurahan Besar Kecamatan Medan Labuhan - Meranda Manalu; Asriwati Asriwati; Nur Aini (Jurnal Kesehatan Amanah, 2025)
Food hygiene is a critical factor that must be considered when consuming food sold to the public. Improper food handling and processing may lead to contamination by harmful microorganisms. This study aimed to evaluate the hygiene practices of traditional Batak restaurants located in Kelurahan Besar, Medan Labuhan Subdistrict. This research was a descriptive survey study. Data collection was carried out through direct observation, field notes, and interviews with food handlers regarding industrial hygiene in Batak restaurants. The study used a qualitative research design with a phenomenological approach to explore hygiene practices in depth. The findings revealed that Restaurant A had mostly complied with hygiene standards in various aspects such as: location and building conditions, food ingredient selection, raw food storage, food preparation/cooking, cooked food storage, transportation of cooked food, and food serving. These practices were aligned with the guidelines outlined in the Regulation of the Minister of Health of the Republic of Indonesia No. 2 of 2023 on Environmental Health, particularly concerning hygiene and sanitation requirements for restaurants and food establishments. In contrast, Restaurant B had not met most of the hygiene standards in those same areas. The restaurant’s location and building conditions, ingredient selection, food storage, cooking process, food transportation, and serving methods were found to be below the acceptable standard as per the same Ministry of Health regulation. Conclusion: The study concluded that adherence to food hygiene standards plays a crucial role in ensuring food safety. Restaurant owners are advised to consistently maintain hygiene in terms of location and infrastructure, food selection, storage, cooking, transportation, and serving practices.